Field Evaluations of the Efficacy of Distance Plus on Invasive Ant Species in Northern Australia. Issue 4 (9th September 2014) - Webb, Garry A.; Hoffmann, Benjamin D.
Abstract : The efficacy of Distance Plus Ant Bait, containing the insect growth regulator pyriproxyfen, was tested in the field against two invasive ant species in northern Australia: African big-headed ant ( Pheidole megacephala (F.)) and yellow crazy ant ( Anoplolepis gracilipes (Fr. Smith)). Results were also gained for a third pest species, Singapore ant ( Monomorium destructor (Jerdon)), from one trial focused primarily on P. megacephala . Five studies were conducted throughout northern Australia, each with different protocols, but common to all was the broad-scale dispersal of Distance Plus, coupled with long-term monitoring of ant population levels. Additionally, a laboratory trial was conducted to assess if there was a direct toxic effect by the bait on A. gracilipes workers, and ant community data were collected at some sites in the A. gracilipes trial to assess nontarget impacts and subsequent ecological recovery. All three species were greatly affected by the treatments. The abundance of P. megacephala declined dramatically in all trials, and by the final assessment for each study, very few ants remained, with those remaining being attributable to edge effects from neighboring untreated properties. At both sites that it occurred, M. destructor was initially at least codominant with P. megacephala, but by the final assessment, only three M. destructor individuals were present at one lure at one site, and only a single individual at the other site. Abundance of A. gracilipes fell, on average, to 31% of control levels by 91 d and then slowly recovered, with subsequent treatments only providing slightly greater control. No direct toxic effect on workers was found in the laboratory trial, indicating that population declines of A. gracilipes were typical bait-related declines resulting from reduced worker replacement. Nontarget impacts of the bait could not be distinguished from the negative competitive impacts of A. gracilipes, but there was a noticeable absence of some key common ant species posttreatment, which was more likely the result of baiting rather than competitive exclusion. The species composition of treated and untreated sites was statistically indistinguishable in multivariate analysis within 2 yr posttreatment, indicating ecological recovery. Our findings indicate that Distance Plus has great potential for invasive ant management.